Forensic accounting and corporate productivity in Thailand: roles of fraud detection, risk reduction and digital capability / Laphatrada Pitchayatheeranart and Kornchai Phornlaphatrachakorn - Pitchayatheeranart, Laphatrada; Phornlaphatrachakorn, Kornchai (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
The objective of this study was to examine the influences of forensic accounting on corporate productivity through fraud detection and risk reduction as the mediators and digital capability as the moderator. In this study, 460 listed firms in Thailand were the sample. Both structural equation model and multiple regression analysis were utilized to investigate the research relationships. This study presented that forensic accounting had a significant positive influence on fraud detection, risk reduction and corporate productivity. Fraud detection positively influenced risk reduction but did not influence corporate productivity. Next, risk reduction had a positive influence on corporate productivity, and it was an important mediator of the forensic accounting-corporate productivity relationships. In addition, digital capability was a significant moderator of the fraud detection-corporate productivity relationships and the risk reduction-corporate productivity relationships. Therefore, forensic accounting has become a key business tool in helping firms achieve sustained goals. Firms are encouraged to support and promote the application of forensic accounting in their organisations in order to succeed and survive for sustainable business strategies, technics and operations under rigorously turbulent environments.